2009
DOI: 10.1158/0008-5472.can-08-2360
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Recruited through CCL22/CCR4 Are Selectively Activated in Lymphoid Infiltrates Surrounding Primary Breast Tumors and Lead to an Adverse Clinical Outcome

Abstract: Immunohistochemical analysis of FOXP3 in primary breast tumors showed that a high number of tumor-infiltrating regulatory T cells (Ti-Treg) within lymphoid infiltrates surrounding the tumor was predictive of relapse and death, in contrast to those present within the tumor bed. + , and CD8 + T cells was documented within lymphoid infiltrates. Altogether, these results show that Treg are selectively recruited within lymphoid infiltrates and activated by mature DC likely through TAA presentation, resulting in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
487
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 631 publications
(523 citation statements)
references
References 46 publications
29
487
3
4
Order By: Relevance
“…Most human tumors are infiltrated by Treg, presenting as small cells, with lymphocytic morphology, and high FOXP3 labeling in their nucleus (Table 1). FOXP3 þ cells were sometimes localized in the vicinity of tumor cells, but rather predominant in the peripheral lymphoid-enriched areas (Curiel et al, 2004;Mizukami et al, 2008;Gobert et al, 2009). The density of FOXP3 þ cells was reported to be significantly higher in malignant than in normal tissue (Bates et al, 2006;Hiraoka et al, 2006;Miller et al, 2006;Mizukami et al, 2008).…”
Section: Foxp3 and Tregs In Human Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Most human tumors are infiltrated by Treg, presenting as small cells, with lymphocytic morphology, and high FOXP3 labeling in their nucleus (Table 1). FOXP3 þ cells were sometimes localized in the vicinity of tumor cells, but rather predominant in the peripheral lymphoid-enriched areas (Curiel et al, 2004;Mizukami et al, 2008;Gobert et al, 2009). The density of FOXP3 þ cells was reported to be significantly higher in malignant than in normal tissue (Bates et al, 2006;Hiraoka et al, 2006;Miller et al, 2006;Mizukami et al, 2008).…”
Section: Foxp3 and Tregs In Human Cancersmentioning
confidence: 99%
“…(1) Treg from the thymus, lymph nodes, bone marrow and peripheral blood express CC-chemokine receptor 4 (CCR4) and can be attracted by the abundant expression of CC-chemokine ligand 22 (CCL22, a CCR4 ligand) produced by cancer cells and tumor-infiltrating macrophages (Curiel et al, 2004;Miller et al, 2006;Mizukami et al, 2008;Gobert et al, 2009). (2) Even if Treg are refractory to proliferation when activated by antibodies against CD3 and CD28 in vitro, they could proliferate actively when located in the tumor stroma, probably under the effect of IL-2 released in the tumor microenvironment and TCR activation by dendritic cells recognizing tumorspecific antigens (Gobert et al, 2009). In experimental tumor models, we demonstrated that a subset of immature myeloid dendritic cells was recruited in the tumor and induced an active proliferation of Treg through TGF-b expression (Ghiringhelli et al, 2005).…”
Section: Foxp3 þ Treg Accumulation In Human Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Elevated levels of CCL22 have been described in many human tumors, including B-CLL, Hodgkin lymphoma, breast, lung and gastrointestinal cancers. [9][10][11][12][13][14] For many of these tumors, elevated intratumoral CCL22 concentrations are associated with a higher tumor infiltration by Treg. Treg are an inhibitory subset of T helper cells, whose function is to suppress cytotoxic T effector cell functions, [15][16][17] involving cell-contact dependent and cell-contact independent mechanisms such as consumption of IL-2, expression of the cellsurface antigen CTLA-4 and secretion of inhibitory cytokines such as TGF-b and IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CCL22 is a prominent chemotactic agent driving Treg accumulation in tumors, and antagonism of either CCL22 or its receptor (CCR4) has potent antitumor effects (18)(19)(20)(21). Similarly, CCL22 expression in allografts promotes Treg accumulation and prevents graft rejection (20,22,23), and induction of CCL22 in the pancreas of nonobese diabetic mice promoted Treg accumulation, protecting against tissue destruction and autoimmune diabetes (24).…”
mentioning
confidence: 99%